Políticas públicas de educação e os desafios da classe trabalhadora : limites e contradições na elaboração do projeto “A Escola Democrática e Popular : a educação que queremos” - Santos, Damião Oliveira (2014)
This study forms part of a research line: "History, Society and Educational Thinking" of the post graduation center of studies in Education at the Federal University of Sergipe whose objective is to analyse the role of the State in the implementation of Educational Policies in the state of Sergipe and the importance of the Workers' Union as element of opposition to the principles and values of ideological assumptions neoliberal politics. It is a study whose theoretical-methodological basis is on the "Historical Materialism Dialectic" (Karl Max) from the curricular reference prepared by the State Department of Education of the State of Sergipe and from the project "Popular and Democratic School: The Education we want" drafted by the Workers' Union in Education of the State of Sergipe System (SINTESE - Sindicato dos Trabalhadores em Educacao da Rede Oficial de Sergipe) to point out the limits and contradictions that are configured in such documents.